Relationship of lumbar vertebral volumetric bone mineral density with trunk muscle density assessed by quantitative computed tomography in maintenance hemodialysis patients - Lijiao Yang; Liping Zhang; Xiaoguang Cheng; Ling Wang; Chao Wang; Dongliang Zhang (Renal Failure)
Background Sarcopenia due to abnormal muscle metabolism and osteoporosis due to abnormal bone metabolism are common complications in maintenance hemodialysis (MHD) patients. The aim of this study was to investigate the association between volumetric bone mineral density (vBMD) and trunk muscle density, as assessed by quantitative computed tomography (QCT) in MHD patients.Methods A total of 108 patients were included. Patients were categorized into a nonosteopenia (n = 38) and an osteopenia group (n = 70) on the basis of vBMD. Multivariate logistic regression was employed to adjust for potential confounding factors.Results Patients in the osteopenia group were older (65.03 ± 10.05 vs. 53.16 ± 13.52 years, p < 0.001). Trunk muscle density (24.97 ± 7.14 vs. 32.04 ± 5.79, p < 0.001) were lower in the osteopenia group than in the nonosteopenia group. Multiple linear regression revealed a positive correlation between trunk muscle density and lumbar vBMD (B = 2.362; 95% CI (1.325–3.399), p < 0.001). Logistic regression analysis revealed that patients with greater trunk muscle density had a lower risk of osteopenia (odds ratio [OR] = 0.842; 95% CI (0.713–0.995), p = 0.043). The predictive value of trunk muscle density for osteopenia in MHD patients was 0.779 (p < 0.001).Conclusions We found that the greater the trunk muscle density is, the greater is the vBMD of the lumbar spine in MHD patients. This may indicate that trunk muscle density serves as a protective factor against osteopenia in this population.